EFQM excellence model as the TQM model of the construction industry of southeastern Europe - Vukomanovic, Mladen; Radujkovic, Mladen; Nahod, Maja Marija (Journal of Civil Engineering and Management, 2014)
Over the years the European Foundation for Quality Management Excellence model (EFQM) has become a popular performance management tool and representation of Total Quality Management (TQM) in Europe. Although the model has been tested and supported by many questionnaire surveys, EFQM has never been validated on real self-assessment scores obtained from companies. Therefore this study validates the model on scores from 34 construction companies in South Eastern Europe. The analysis shows that: a) there is an enabler excellence construct that is obtained by each enabler criteria; b) there is a result excellence construct that is obtained by each result criteria; and c) the EFQM model is most suitable for Contractor type organizations. Furthermore, we have found that the EFQM weights do not entirely correspond with the construction industry. Therefore we present new weights for the better use in the construction. Although this study proves EFQM to be a good representation of TQM in the construction industry, further improvements are needed. This is especially evident within investor and consultant type organization, where the criteria of Policy and Strategy, Leadership and Processes, People results and Client results showed certain limitations.